Presence of pleural adhesions can predict conversion to thoracotomy and postoperative surgical complications in patients undergoing video-assisted thoracoscopic lung cancer lobectomy - Li, Shuang-Jiang; Zhou, Kun; Wu, Yan-Ming; Wang, Ming-Ming; Shen, Cheng; Wang, Zhi-Qiang; Che, Guo-Wei; Liu, Lun-Xu (Journal of Thoracic Disease, 2018)
Background: The purpose of our cohort study was to investigate the effects of pleural adhesions on perioperative outcomes in patients undergoing video-assisted thoracoscopic surgery (VATS) lobectomy for non-small-cell lung cancer (NSCLC). Methods: We performed a single-center retrospective analysis on the prospectively-maintained dataset at our unit from February 2014 to November 2015. Patients were divided into two groups (Group A: presence of pleural adhesions; Group B: absence of pleural adhesions) according to our grading system of pleural adhesions when entering the chest cavity. Demographic differences in perioperative outcomes between these two groups were initially estimated. A multivariate logistic-regression analysis was then performed to confirm the predictive value of the presence of pleural adhesions. Results: A total of 593 NSCLC patients undergoing VATS lobectomy were enrolled. The conversion and postoperative morbidity rates were 3.2% and 29.2%, respectively. There were 154 patients with pleural adhesions (Group A) and 439 patients without pleural adhesions (Group B). Group A patients had significantly higher rates of conversion to thoracotomy (9.1% vs. 1.1%; P